Gender-Responsive Entrepreneurial Orientation and FinTech Adoption in MSMEs: Examining the Moderating Role of Triple Bottom Line Principles - Heriberta; Rike Setiawati; Yayuk Sriayudha; Ade Octavia; Dwi Hastuti (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
MSMEs are pivotal to Indonesia’s economy, yet many face challenges in achieving long-term sustainability, particularly in balancing economic, social, and environmental outcomes. The study specifically examines the direct effects of gender-responsive entrepreneurial orientation and fintech adoption on MSME sustainability, as well as the indirect effects moderated by triple bottom line dimensions. Primary data were collected via structured surveys from MSME owners and managers who have implemented gender-inclusive entrepreneurial practices and fintech solutions. Structural Equation Modeling using SmartPLS was employed to test both the direct and moderation relationships. The results indicate that gender-responsive entrepreneurial orientation and fintech positively influence MSME sustainable performance, with the triple bottom line moderating these effects. Notably, the social dimension of the triple bottom line amplifies the impact of gender-responsive entrepreneurial orientation, while the economic and environmental dimensions strengthen the influence of fintech adoption. These findings offer actionable insights for policymakers, practitioners, and MSME stakeholders by highlighting the importance of integrating gender-inclusive strategies and digital financial solutions to enhance competitiveness, social impact, and long-term sustainability.